The Role of Organizational Culture, Work Environment and Motivation in Improving Employee Performance - Edy Jumady (Yayasan Pendidikan Bukhari Dwi Muslim, 2022)
This research was conducted to analyze the influence of organizational culture, work environment and motivation on the performance of the employees of RSUP Dr. Wahidin Sudirohusodo Makassar and To analyze the most dominant variables influencing the performance of RSUP employees. Dr. Wahidin Sudirohusodo Makassar. The first hypothesis of this research is that organizational culture, work environment and motivation have a significant effect on the performance of RSUP employees. Dr. Wahidin Sudirohusodo Makassar. Researchers used a quantitative approach designed to determine whether organizational culture, work environment and motivation as independent variables affect employee performance. The research emphasizes on measuring variables with numbers and analyzing data with statistical procedures using multiple linear regression analysis with the help of SPSS 16.0 program. The type of data in this study is the type of subject data obtained in the form of opinions, attitudes, experiences and characteristics of the respondents who are the research subjects. To obtain the expected research results the authors use data collection methods in the form of observation, interviews, questionnaires and documentation. The results of the study are organizational culture, work environment and motivation have a positive and significant influence on employee performance. When the application of organizational culture, work environment and motivation improves, employee performance will increase and to achieve this, a better socialization/understanding of the values in the organizational culture is carried out. When the work environment is getting better and more conducive, the performance of RSUP employees will also increase. Dr. Wahidin Sudirohusodo Makassar. This situation indicates that the work environment is an important factor in improving employee performance.